2013
DOI: 10.1007/s11121-013-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

Youth Misperceptions of Peer Substance Use Norms: A Hidden Risk Factor in State and Community Prevention

Abstract: Effective community prevention of substance abuse involves the integration of policies and programs to address many different risk and protective factors across the social ecology. This study sought to examine whether youth perceptions of peer substance use norms were operating as a risk factor at the same level as other known risk factors in a statewide community prevention effort. Several different analytical techniques were employed to examine the self-reported data from a sample of over 8,000 students in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In addition, school psychologists and school communities can deliver interventions that target perceived peer norms of use and improve perceptions of school climate. For instance, interventions that address and change perceived peer norms at the school level may impact individual level factors that lead to substance use initiation and may signal the need for macro-level interventions such as a social norms marketing campaign (Wambeam et al, 2014). Structural interventions can bring about normative shifts in how people view substance use and can potentially produce widespread effects (Fisher, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, school psychologists and school communities can deliver interventions that target perceived peer norms of use and improve perceptions of school climate. For instance, interventions that address and change perceived peer norms at the school level may impact individual level factors that lead to substance use initiation and may signal the need for macro-level interventions such as a social norms marketing campaign (Wambeam et al, 2014). Structural interventions can bring about normative shifts in how people view substance use and can potentially produce widespread effects (Fisher, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have found that adolescents’ own substance use was more influenced by perceived views of their peers’ use than by their peers’ actual use (Duan et al, 2009). In regards to perceived peer substance use norms, studies have found that as youth levels of misperception increase, substance use likelihood increases (Wambeam, Canen, Linkenbach, & Otto, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, a longitudinal study with 2248 students in the United States and Australia, documented that youth who perceived drug use as common among their peer groups were more likely to use tobacco and marijuana than their counterparts (Eisenberg, Toumbourou, Catalano, & Hemphill, 2014). Moreover, studies have found that youth are more likely to overestimate the number of peers engaged in substance use and other problem behaviors (Eisenberg et al, 2014; Wambeam, Canen, Linkenbach, & Otto, 2014). Social learning theory would suggest that peer group affiliation would reinforce dominant peer norms and that youth are more likely to adopt such behaviors in order to gain and maintain group membership (Petraitis, Flay, & Miller, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…W. Perkins, Meilman, Leichliter, Cashin, & Presley, 1999; H. W. Perkins & Craig, 2012; Wambeam, Canen, Linkenbach, & Otto, 2013). The consistent tendency is to overestimate the extent or prevalence of more permissive attitudes and problem behaviors than exist, even in peer contexts where substance use is actually relatively high.…”
mentioning
confidence: 99%